Prevalence and clinical characteristics of otitis externa among patients attending Otorhinolaryngology Department at Muhimbili National Hospital, Tanzania - Abraham, Zephania Saitabau; Tarimo, Onesmo; Kahinga, Aveline Aloyce; Ntunaguzi, Daudi; Mapondella, Kassim Babu; Massawe, Enica Richard (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Otitis externa is among the otological diseases with significant impact on the quality of life of sufferers. Little is known in Sub Saharan countries despite being the focus of such disease. The study aimed to determine the prevalence and clinical characteristics of otitis externa at Muhimbili National Hospital, Tanzania’s largest tertiary hospital. Methods: This was a hospital based descriptive cross sectional study where 1200 participants were recruited from June 2016 to January 2017. Data was analyzed using SPSS program version 20. Results: A total of 1200 patients were recruited in this study and majority 601(50.1%) were females. Majority 672(56%) were in age group 0–10 years. Among 1200 patients, 138 (11.5%) were diagnosed to have otitis externa and male predominance (55.1%) was found. Majority 120 (87%) had diffuse otitis externa and with 0-10 years (25.83%) being the commonly affected age group by variant. The commonest risk factor was self-ear cleansing 87(53.7%) and only 2.9% were found to have complications of otitis externa. Conclusions: Otitis externa was found to be prevalent and with male predominance. Self-ear cleansing was the commonest risk factor. Complications of otitis externa were found to be rare. Public awareness on otitis externa should be advocated in our country.